'In it for the long run': sources of self-efficacy in adolescent female athletes. Issue 2 (20th January 2011) - Watson, L; Binks, E; Kawycz, S
Abstract : Introduction: Most research in sport psychology investigating the sources of efficacious beliefs has been conducted within the parameters of Bandura's (1977) self-efficacy theory.1 Within the context of a situation six sources are believed to be cognitively appraised; mastery performances, vicarious experiences, verbal persuasion, imaginal experience, emotional states and physiological states, to develop one's efficacy expectations and goal directed behaviour.2 The aim of the study was to identify the sources of self-efficacy most salient to female adolescent long distant runners, why such sources are selected and whether they were interlinked. Method: Semi-structured interviews were conducted to allow athletes' sources and types of efficacy to emerge inductively. Interviews were recorded, transcribed verbatim and analysed using the interpretative phenomenological approach. After obtaining ethical approval, six female adolescent athletes (mean age=15 years, national level) were recruited, using opportunistic sampling, from a single running club. Results: Nine sources emerged from this investigation with numerous variations within them being exclusive to sport and female adolescent athletes. The nine sources of self-efficacy identified were: performance accomplishments, vicarious experiences, verbal persuasion, physiological experiences, imaginal experiences, emotional states, situational favourableness, self-perception and athlete specific. Specifically, it was found that performance accomplishments provide a catalyst for the additional sources. In particular performance accomplishments inform the athlete efficacious beliefs, however this is only situational specific and is none transferable. Individual differences arose as an imperative factor in how one interprets the efficacious sources. Conclusion: The results extend previous conceptualisations related to personal efficacy beliefs within athletic settings and supported the contention that efficacious beliefs play a significant moderating effect on athlete functioning and athletic performance. Findings highlight the need to further examine the uses of multiple sources of self-efficacy and their weighting in individual's sports, as this may provide valuable insight for coaches and sports psychologists working with particular athlete groups and assist in developing interventions which augment or maintain efficacious beliefs in individual athletes.